Impact of afatinib dose modification on safety and effectiveness in patients with EGFR mutation-positive advanced NSCLC: Results from a global real-world study (RealGiDo). (January 2019) - Halmos, Balazs; Tan, Eng-Huat; Soo, Ross A.; Cadranel, Jacques; Lee, Min Ki; Foucher, Pascal; Hsia, Te-Chun; Hochmair, Maximilian; Griesinger, Frank; Hida, Toyoaki; Kim, Edward; Melosky, Barbara; et al.
Highlights: Real world data on afatinib safety are consistent with clinical trial data. Afatinib dose adjustment reduced the frequency/intensity of adverse drug reactions. Modified dosing had no impact on effectiveness. 18.7 months' time on treatment, even with 12% poor performance status patients. Abstract: Objectives: In the LUX-Lung clinical trials of afatinib in EGFR mutation-positive NSCLC, tolerability-guided dose adjustment reduced the incidence and severity of adverse events while maintaining efficacy. The RealGiDo study evaluated the impact of afatinib dose adjustment in a real-world setting. Materials and methods: This non-interventional, observational study used medical records of EGFR mutation-positive NSCLC patients treated with first-line afatinib. Primary outcomes were adverse drug reaction (ADR) incidence and severity, time to treatment failure (TTF), and time to progression (TTP), relative to LUX-Lung 3 (LL3). Results: 228 patients were enrolled from 13 countries. Baseline characteristics were in line with LL3 but with more Del19 patients (78.1% vs. 49.0%) and fewer Asian patients (43.9% vs. 72.2%); 11.8% had ECOG performance status 2–3. A total of 71 (31.1%) received a modified starting dose of ≤30 mg. Of patients who started with 40 mg, 67.1% underwent dose reductions, 86.5% of which were in the first 6 months. Dose reductions were mainly due to ADRs and were more common in female, East Asian, and low body-weight patients. There were no new safety signals and fewer ≥grade 3 ADRs (28.4% vs. 48.9%) and serious adverse events (5.2% vs. 14.0%) than in LL3. Median TTF and TTP were 18.7 and 20.8 months, respectively, and were not impacted by reduced starting dose or dose modification. Conclusion: Real-world data show that afatinib dose adjustments reduced the frequency and intensity of ADRs without compromising effectiveness, highlighting the benefit of tailoring afatinib dose to optimise treatment outcomes and supporting clinical decision-making. The study is registered at clinicaltrials.gov (NCT02751879).